Analisis Kualitas Layanan Restoran dengan Metode SERVQUAL (Service Quality) IPA (Importance Performance Analysis) dan QFD (Quality Function Deployment) - Mohammad Setiawan Mohammad Setiawan (Journal of Industrial View, 2023)
Kartikasari Restaurant is a catering business engaged in foreign fast food with a favorite menu of Chinese food, this business was established around 1992. In 2005 this company began to develop European cuisine because it often received tourist guests. The problem that is happening now is the poor quality of service because seen from the results of the customer expectation survey, restaurants are only able to provide 85% service while service providers usually provide 95% worth of services, from the decline in these services it is necessary to make improvements because every day customer requests are increasing. increaseThe method used in this study is the SERQUAL (Service Quality) method as a step to retrieve data by distributing questionnaires with five attributes to customers with 100 respondents. Furthermore, the gap between customers and service providers will be analyzed using a Quadrant Analyst map using the IPA (Importance Performance Analysis) method. it will show some quality of service that needs to be improved and make an alternative with the QFD (Quality Function Deployment) method.In this study, the highest gap results were found in the attributes RL 06 (-0.174), RL 07 (-0.147), RL 08 (-0.040) RL 10 (-0.080), RS 11 (-0.134), RS 12 (-0.080), RS 13 (-0.053) and RS 15 (-0.133). Whereas in the Cartesian diagram quadrant 1 (top priority) has the same value as the results of the gap, the improvement is by developing the abilities of all employees, as well as fostering a sense of security and comfort, fostering a sense of empathy, politeness, sense of responsibility and discipline